Behavioural isolation may facilitate homoploid hybrid speciation in cichlid fish. (23rd December 2013) - Selz, O. M.; Thommen, R.; Maan, M. E.; Seehausen, O.
Abstract Hybrid speciation is constrained by the homogenizing effects of gene flow from the parental species. In the absence of post‐mating isolation due to structural changes in the genome, or temporal or spatial premating isolation, another form of reproductive isolation would be needed for homoploid hybrid speciation to occur. Here, we investigate the potential of behavioural mate choice to generate assortative mating among hybrids and parental species. We made three‐first‐generation hybrid crosses between different species of African cichlid fish. In three‐way mate‐choice experiments, we allowed hybrid and nonhybrid females to mate with either hybrid or nonhybrid males. We found that hybrids generally mated nonrandomly and that hybridization can lead to the expression of new combinations of traits and preferences that behaviourally isolate hybrids from both parental species. Specifically, we find that the phenotypic distinctiveness of hybrids predicts the symmetry and extent of their reproductive isolation. Our data suggest that behavioural mate choice among hybrids may facilitate the establishment of isolated hybrid populations, even in proximity to one or both parental species.